(untitled) (L’architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2016)
This paper considers the foundation of Rome and the figure of Romulus, the Founder, imagining the latter as a contemporary architect facing the relevant problems of unfounded settlements. Contemporary cities are often unfounded because their public spaces have lost any relations with the architecture of Earth. The act of foundation produces an architectural representation of the geomorphological features of the founded site that is technically developed within the cartographic space of the architectural design. Through the studies of Andrea Carandini about the foundation of Rome and the thought of Michel Serres about the idea of foundation in the western world, the paper affirms the necessity of re-thinking the role of foundation as a project that returns many times during the life of settlements (â€œlike a refrainâ€, writes Serres) and that every time describes the architecture of the Earth. Like the sprawled villages that constituted archaic Rome, our sprawled settlements can be re-designed by the means of foundation design able to attribute an identifying value to public spaces. In analogy with the concept of â€œidentity representationâ€ proposed by Alberto Magnaghi, public spaces could become architectural representation of those geomorphological features of places that enhance the identity of communities. Â